(untitled) (American Journal of Islam and Society, 2011)
The current discourse on bioethical questions often reveals a certain patchiness or seeming inability to answer contemporary bioethical problems within an Islamic epistemological paradigm. Attempting to analyze the causes of this phenomenon, the author describes the decontextualization of Islamic concepts from a background of secularized medical care and the ethics in the Islamic world—as well as the estrangement due to these questions of Islamic law from its holistic framework of application as a pervasive phenomenon, which brought about the dilemmas of bioethics in the twenty-first century. The author discusses chosen bioethical case studies in this light, with a focus on the concept of brain death. Doing so, the author takes into consideration the paradigmatic relationship between science, bioethical models, and the implications of the relevant different worldviews. The author shows how constructed realities related to the life sciences have been imported from the secular setting into an already estranged Islamic context to be answered, and describes the evolving dilemmas that make Islamic bioethics appear like a stranger moving in a strange land.